Archived

This topic is now archived and is closed to further replies.

leinad

quaternion basis products

Recommended Posts

given i2 = j2 = k2 = -1 = i*j*k therefore i = j*k = -k*j j = k*i = -i*k k = i*j = -j*i I see how we arive at i = j*k, b/c i2 = i*j*k, so i*i/i = i*j*k/i, and finally i = j*k. But I don''t see how you get the sign when you revert the order of multiplication. FYI, I''m getting this out of Andre Lamothe''s great new book. I still can''t find (in this 1700 pg book) where he show you how to use quaternions for camera manipulation.

Share this post


Link to post
Share on other sites